Kesan komitmen pekerja terhadap hubungan antara tingkah laku kepimpinan dan keberkesanan organisasi - Isa, Khairunesa (2013)
Past research has mostly focused on the impact of leadership style on organizational effectiveness. However, the role of employee commitment such as absenteeism, turnover or discipline problem as a mediator has been neglected. The objective of this study is to determine the relationship between the transformational and transactional leadership style and the organizational effectiveness, and to identify the effect of employee’s commitment as a mediator, either as a partial or full mediator in the relationship between the leaders’ behaviors. A total of 130 custom officers were selected based on purposive sampling to participate in the survey. The instruments used were: Multifactor leadership Questionnaire to measure the respondents’ perceptions towards the transformational and transactional leadership style, a Three-Component Model of Employee Commitment to measure the employees’ commitment, and Index of Perceived Organizational Effectiveness to measure the organizational effectiveness. Frequency distribution and percentages to describe respondents’ demographic were analysed using descriptive statistics while the relationship between transformational and transactional leadership style and the organizational effectiveness were analysed using Pearson Correlation and Multiple Regression. For the purpose of determining the effect of employee’ commitment as a mediator, three regression equations based on Baron and Kenny model were run through Multiple Regression Analyses. Results revealed that the transformational and transactional leadership style had a moderate relationship with the organizational effectiveness and contributed only 23% to the effectiveness of the organization. Employee commitment was found to have a partial mediate effect in the relationship between leadership style and the effectiveness of the organization. This study has provided some insights on the importance of leadership style and the effect of employees' commitment to enhance the effectiveness of an organization.